PENGARUH KUALITAS PELAYANAN, SANKSI PERPAJAKAN, KEMUDAHAN PEMBAYARAN, DAN RAZIA LAPANGAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR RODA DUA (Studi Kasus pada Kantor Bersama SAMSAT Klatenï© - Wulandari, Dewi Muharromah; Sulistyowatie, Syska Lady; Santosa, Imam (KIAT BISNIS, 2017)
This research aim to to know the influence of simultan and also parsial from service quality, taxation sanction, payment amenity, and razia field to taxpayer compliance in paying Iease of motor vehicle of wheel two. Research use the primary data as much 100 sampel with the method of determination of sampel accidental sampling, that is taxpayer payment of lease of Motor Vehicle which coincidence met at the research technique analyse by using doubled linear analysis regresi, test the F (simultan), test the t (parsial), and test the coefficient determinasi (R2). Result of research indicate that the existence of influence signifikan by simultan service quality, taxation sanction, payment amenity, and razia field to taxpayer compliance in paying Iease of motor vehicle of wheel two at office with SAMSAT Klaten. While by parsial is taxation sanction have an effect on the signifikan to taxpayer compliance in paying Iease of motor vehicle of wheel two, but service quality, payment amenity, and razia field do not have an effect on to taxpayer compliance in paying Iease of motor vehicle of wheel two. Keyword: Service Quality, Taxation Sanction, Payment Amenity, Razia Field, Tax payer Compliance